What the public wants to know about the recycling of contaminated soil - Stephen Takeshi Terada; Hitomi Matsunaga; Aizhan Zabirowa; Tomoko Watanabe; Yuya Kashiwazaki; Makiko Orita; Thierry Schneider; Noboru Takamura (PLoS ONE, 2025)
After the Fukushima Daiichi Nuclear Power Plant accident of March 11, 2011, the Japanese government implemented a soil decontamination program as part of disaster area recovery. This resulted in approximately 14 million cubic meters of contaminated soil being stored in an interim facility in Fukushima. Management of the soil has included radioactivity measurement, separation and screening. When recycled the soil may be used in public works projects, but the public objected to soil recycling demonstration projects planned for the Tokyo metropolitan area, and the use of recycled soil in their communities. This study seeks to understand key factors associated with the public’s desire for more information about soil recycling. We conducted a nationwide survey and received 5257 responses from people between the ages of 18 and 89 living in the country’s 47 prefectures and eight geographic regions. The results showed that approximately 60% of residents did not want recycled soil to be relocated near where they live. A large number (75.9%, n = 3991) of respondents had never received information on radiation and its health effects, while 66.1% (3473) of respondents wanted more information about recycled soil. Those who wanted more information about soil recycling prioritized learning of its health effects, effects on food and water, environmental effects, radioactivity levels and monitoring methods, and intergenerational health effects. A binary logistic regression analysis clarified several independent factors related to wanting more information, including interest in the recovery of the area surrounding the FDNPP, receipt of information on radiation and its health effects, and the belief that the FDNPP accident will result in intergenerational health effects. The study results provide a greater understanding of the public’s information needs and can help to improve communication and understanding related to this controversial topic.